(3PGJ GdMdd hegGI Gdcdds - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s ((3eMeO Hf YHO Gdefge Hf Ydi GdbQTi s)
(3ChdgG (B:s
(3HMeO Gddg QH GdYGdejf hQH GdYQT GHOG eSJYjfG hHYO aEffi CXgQJ eGdhMhGg ShGi cGf Hg NfjfG s
(3BNQgG (B:s
(3hMSHi LhO QHi hGdJLGAi Edjg deG Ched Cf jchfG JeJ PGJ GdMdd hegGg Gdcdd hHJeGegG Je GdcJGH s
(3GdfSNI HgG MhGTs
(3hgj bUjOI ai GdCdZGR eY TQMgGs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
Keywords: (3GdfMhs